Climate change and Pacific islands : indicators and impacts : report for the 2012 Pacific Islands Regional Climate Assessment (PIRCA) - Keener, Victoria W. (National climate assessment regional technical input report series., 2012)
"Climate Change and Pacific Islands: Indicators and Impacts is being published as one of a series of technical inputs to the National Climate Assessment (NCA) 2013 report. Developed by the Pacific Islands Regional Climate Assessment (PIRCA), this report assesses the state of knowledge about climate change indicators, impacts, and adaptive capacity of the Hawaiian archipelago and the US-Affiliated Pacific Islands (USAPI). The PIRCA is a collaborative effort engaging federal, state, and local government agencies, non-government organizations, academia, businesses, and community groups to inform and prioritize their activities in the face of a changing climate."